CHINESE TOURISM IN THAILAND: EXPERIENCES AND SATISFACTION - WALSH, JOHN (ASEAN Journal on Hospitality and Tourism, 2007)
Tourism research in Thailand is unbalanced, since it largely focuses on western travellers and pays very little attention to Asian tourists, especially mainland Chinese tourists, whose numbers and value are rising year-on-year. The connections between China and Thailand are many-stranded and more than a thousand years old. However, there is very little understanding of what kind of experience Chinese tourists would like to receive and whether they enjoy their visits. This paper reports on a quantitative survey of 250 Chinese tourists in Thailand which investigated the kinds of experience that they received and the degree to which they were satisfied with them. It was found that most travellers, although they no longer are subject to ‘zero-dollar tourism,’ nevertheless face constant appeals to buy often unwanted products and must accept very low levels of service. Satisfaction levels are, consequently, varied.